Genetic variation of tropical corn inbred lines for silage production - Ibrahim, Syazreena (2015)
A study was conducted to evaluate the genetic variation of eight tropical corn (Zea mays L.) inbred lines and one control variety (Hybrid 530). The study was conducted at Field 10, Faculty of Agriculture, Universiti Putra Malaysia and arranged in randomized complete block design (RCBD) with three replications. The objectives of this study were to evaluate the agronomic performance of selected inbred lines for silage purposes, estimate the heritability and correlation among traits measured and assigning the inbred lines into heterotic groups. Sixteen data on yield and agronomic traits were recorded. Analysis of variance indicated significant effects for inbred lines or genotype for all traits measured except for crude protein content in leaves and in stems, while blocks effects were not significant for all traits measured except for crude protein content in leaves. Means comparison of the traits showed that inbred lines CML152 and CML160 showed highest mean value in most of the traits measured except for days to tasseling, days to silking, and number of leaves per plant. The heritability estimates were ranged from low to high value (27.5% to 93.7%). Fresh leaf yield was found to be the most heritable trait (93.7%) followed by dry leaf yield (93.5%), dry stem yield (90.8%), fresh ear yield (90.8%), dry plant yield (88.4%), fresh plant yield (87.7%), dry ear yield (86.6%), plant height (85.6%), number of leaves per plant (82.8%), ear height (76.0%), fresh stem yield (75.5%), crude protein content in ears (73.5%), days to tasseling (63.8%) and days to silking (57.4%), while crude protein content in leaves showed the lowest heritability estimate among the traits measured (27.5%). In the correlation study, fresh plant yield was found to be highly significantly correlated with most of the traits (at p<0.01) except for crude protein content in leaves, plant height, number of leaves per plant and days to tasseling. Four heterotic groups were formed using SAHN cluster analysis by UPGMA method based on their performance per se. In conclusion, the inbred lines evaluated revealed wide genetic variations for yield and agronomic traits. These variations can be further exploited toward the production of corn hybrid for silage utilization.